Sabaic lexical survivals in the Arabic language and dialects of Yemen - Müller, Walter W. (Proceedings of the Seminar for Arabian Studies, 2014)
At the beginning of Sabaean studies in the last quarter of the nineteenth century scholars noticed words in the inscriptions, which had parallels not in Classical Arabic but in the dialects of Yemen. Experts including David Heinrich Müller, Eduard Glaser, and Carlo de Landberg paid special attention to lexical links between the extinct and extant languages of southern Arabia. Ettore Rossi checked the glossary in Carolus Conti Rossini's Chrestomathia Arabica Meridional is Epigraphica (1931) and provided numerous lemmata with words taken from Yemeni dialects. The authors of the Sabaic Dictionary (1982) marked some entries with the Arabic letter >> ä' to denote the modern Yemeni usage ofthat word. It was Ibrahim Al-Selwi's aim in his doctoral dissertation (1987) to collect Yemeni words from the writings of the two medieval South Arabian authors, Al-Hamdânï and Nashwân al-Himyarï, many of which go back to pre-Islamic times. In the three parts of his glossary of northern Yemeni Arabic dialects (1992-2006), Peter Behnstedt indicated etymological correspondences in Epigraphic South Arabian for a number of words, which he had found in the Sabaic Dictionary. Mutahhar al-Iryānī occasionally pointed to parallels in the ancient inscriptions in the two editions of his Mu'jam al-Yamani (1996; 2012). Janet Watson (2004) noted the problem of lexical survivals and listed a number of words from ancient South Arabian roots that retained their original Sabaic meaning. Finally it can be recorded that the quantity of old attestations has been considerably increased since the publications of wooden sticks with texts in minuscule script. The Sabaic lexical survivals in the Arabic language and dialects of Yemen, which are dealt with in this article, amount to more than 100. Words that have survived from Sabaic belong mainly to the semantic fields of geographical features, agriculture, irrigation, architecture, building materials, cultural history, and local foodstuffs. Apart from elements of archaic vocabulary the Sabaic substratum also left traces in the morphology, that is, in prepositions and negations and in the so-called k-perfect of some Yemeni dialects.